PENGARUH METODE PEMBELAJARAN SNOWBALL THROWING BERBANTUAN MEDIA GAMBAR TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS V UPT SD NEGERI 87 TAMANROYA KEC. GALESONG UTARA, KAB. TAKALAR - Infaq Wirani, Nur; A Arif, Tarman; Ayu Andhira, Desy (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Abstract This study aims to determine the effect of the Snowball Throwing learning model assisted by image media on the ability to write explanatory texts of grade V students of UPT SD Negeri 87 Tamanroya, North Galesong District, Takalar Regency. This type of research is a pre experimental study which is a quantitative study. The sample in this study was 15 people. The data collection technique used was data on student activities in learning to write explanatory texts collected using student learning activity observation sheets. The data analysis technique in this study was a descriptive analysis technique and a descriptive statistical T-Test and inferential statistics. The results of the descriptive statistical analysis of the use of the Snowball Throwing Learning Model on explanatory text writing skills, explanatory text writing skills assisted by image media using the Snowball Throwing learning method showed better learning outcomes than before the Snowball Throwing learning model assisted by this image media was applied. The results of the inferential statistical analysis using the t-test formula, it is known that the t-count value obtained is 8.33 with a frequency (db) = 15–1 = 14, at a significance level of 5%, t Table = 2.145 is obtained. So, t Count t table or the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is an influence in implementing the Snowball Throwing learning method assisted by image media on the ability to write explanatory texts in class V students of UPT SD Negeri 87 Tamanroya, North Galesong District, Takalar Regency. Keywords: Pre-experiment, Snowball Throwing method Abstrak Penelitian ini bertujuan untuk pengaruh model pembelajaran Snowball Throwing berbantuan media gambar terhadap kemampuan menulis teks eksplanasi siswa kelas V UPT SD Negeri 87 Tamanroya Kec. Galesong Utara, Kab. Takalar. Jenis penelitian ini adalah penelitian pra eksperimen yang merupakan penelitian kuantitatif. Sampel dalam penelitian ini sebanyak 15 orang. Teknik pengumpulan data yang digunakan adalah data tentang aktivitas siswa dalam pembelajaran menulis teks eksplanasi dikumpulkan dengan menggunakan lembar observasi aktivitas belajar siswa.Teknik analisis data dalam penelitian ini adalah teknik analisis deskriptif dan uji T-Test statistik deskriptif dan statistic inferensial. Hasil analisis statistik deskriptif penggunaan Model Pembelajaran Snowball Throwing terhadap keterampilan menulis teks eksplanasi, keterampilan menulis teks ekplanasi berbantuan media gambar dengan menggunakan metode pembelajaran Snowball Throwing menunjukkkan hasil belajar yang lebih baik daripada sebelum diterapkan model pembelajaran Snowball Throwing berbantuan media gambar ini. Hasil analisis statistik inferensial menggunakan rumus uji t, diketahui bahwa nilai t Hitung yang diperoleh adalah 8,33 dengan frekuensi (db) = 15–1 = 14, pada taraf signifikansi 5% diperoleh t Tabel = 2,145. Jadi, t Hitung t tabel atau hipotesis nol (H0) ditolak dan hipotesis alternative (Ha) diterima. Hal ini membuktikan bahwa ada pengaruh dalam menerapkan metode pembelajaran Snowball Throwing berbantuan media gambar terhadap kemampuan menulis teks eksplanasi pada siswa kelas V UPT SD Negeri 87 Tamanroya Kec. Galesong Utara, Kab. Takalar. Kata kunci: Pra-eksperimen, metodel Snowball Throwing